Nanomaterials and devices - Shi, Donglu; Guo, Zizheng; Bedford, Nicholas (Micro & nano technologies., 2015)
Introducing the fields of nanomaterials and devices, and their applications across a wide range of academic disciplines and industry sectors, Donglu Shi bridges knowledge acquisition and practical work, providing a starting point for the research and development of applications. The book describes characterization of nanomaterials, their preparation methods and performance testing techniques; the design and development of nano-scale devices; and the applications of nanomaterials, with examples taken from different industry sectors, such as lighting, energy, bioengineering and medicine / med.